2015
DOI: 10.1002/ejsp.2103
|View full text |Cite
|
Sign up to set email alerts
|

Why are online games so self‐involving: A social identity analysis of massively multiplayer online role‐playing games

Abstract: This article investigates the ways in which players of massively multiplayer online role-playing games (MMORPGs) internalize being a player into their self-concept. In accordance with the social identity framework, we assume that being a player and being a member of a guild within the game can both shape the social identity of members. In two studies, we survey players inside or outside the MMORPG. Players are interviewed either at an interguild comparison level or at the more inclusive level of MMORPG players… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 24 publications
1
21
0
4
Order By: Relevance
“…For players, they would self‐identify and behave as their fellow gamers or perhaps as a player of a specific video game. The research found that players identifying to the in‐game faction they belong to displayed favoritism to other members of the same faction (Guegan, Moliner, & Buisine, ). Conversely, players who belong to perceived outgroups are depersonalized and stereotyped (Postmes, Spears, & Lea, ).…”
Section: Social Identity Model Of Deindividuation Effects and The Gammentioning
confidence: 99%
“…For players, they would self‐identify and behave as their fellow gamers or perhaps as a player of a specific video game. The research found that players identifying to the in‐game faction they belong to displayed favoritism to other members of the same faction (Guegan, Moliner, & Buisine, ). Conversely, players who belong to perceived outgroups are depersonalized and stereotyped (Postmes, Spears, & Lea, ).…”
Section: Social Identity Model Of Deindividuation Effects and The Gammentioning
confidence: 99%
“…El juego contaba con una interfaz gráfica muy intuitiva que apelaba a metáforas conocidas para hacer atractivo el escenario lúdico (Abdulhak, Cha & Kang, 2011), y se ajustaba a los criterios de usabilidad y jugabilidad (Guegan, Moliner & Buisine, 2015), facilitando la navegación e interacción. Mediante ventanas e intuitivos iconos se identificaban los datos de la ciudad y el nivel alcanzado por el jugador, visibilizando la energía, monedas, productos y disponibilidad de dinero, recursos acumulados para mejorar la ciudad, ampliar su población y terrenos, y el inventario de productos.…”
Section: Cityville: Narrativa Centrada En La Construcción De Ciudadesunclassified
“…Para Huang, Huang, Chou y Teng (2017) y O' Connor et al (2015), otro factor que lo afianza es la invitación a pertenecer a la comunidad oficial del juego, pues ello les proporciona un sentimiento de amparo al saberse respaldados por reglas explícitas. Su adscripción a estas comunidades les garantiza la resolución de problemas, el intercambio de experiencias entre jugadores, etc., favoreciendo su sensación de seguridad, lo que les alienta a seguir jugando online (Guegan, Moliner & Buisine, 2015).…”
Section: Motivaciones Y Perfiles De Los Jugadores Virtualesunclassified
See 2 more Smart Citations